Post-mortem detection of a new DOC psychoactive substance in vitreous humor (2017)
Introduction: 2,5-Dimethoxy-4-chloroamphetamine (doc) is a novel psychoactive substance (nps) derived from phenylethylamine with 5-ht receptor agonist activity and hallucinogenic and stimulant properties similar to LSD and amphetamines. DOC has been associated with severe poisoning and death. Materials and methods: Samples from the autopsy were analyzed by immunoassay and gas-liquid chromatography-mass spectrometry (gc-ms) (lc-esi-ms/ms). History of the case: The deceased is a 17-year-old who, after applying a stamp on the eye thinking it was LSD, convulsed several times and died. Results and discussion: The toxico-logical findings were as follows: no LSD or metabolites, amphetamines, 2CB, benzodiazepines, phenothiazines, tricyclic antidepressants or other depressants were detected in cardiac blood, peripheral blood, gastric contents, urine or vitreous humor. The detection of cannabinoids was confirmed in urine. doc was detected in the vitreous humor. Conclusions:The results obtained by the analytical methodology and the lc-esi-ms/ms technique are satisfactory in terms of the spectral identification of the doc molecular structure, and allow to evidence the use of this new psychoactive substance among young people for recreational purposes. Our contribution is to provide the first case documented through the post-mortem toxicological analysis of doc in Colombia. Sharing new toxicological findings is essential not only to improve knowledge, but also to raise awareness of new psychoactive substances such as the phenylethylamine group, among others, in the forensic community.